A GPU-based Architecture for Supporting 3D Interactions - Batagelo, Harlen C.; Shin-Ting, Wu (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2008)
Most direct manipulation tasks rely on precise placements of the cursor on the object of interest. Commonly, this requires the knowledge of application-dependent geometry attributes of this object computed on the CPU. We present a simple yet general GPU-based framework for computing such attributes without depending on application-specific algorithms. It provides, for each pixel of the rendered model, application-defined values and elements of discrete differential geometry computed on the GPU. We show how this framework can support the implementation of many direct manipulation tasks presented in the literature, even when the geometry is modified on the GPU.